IMPLEMENTASI BAHAN AJAR BERBASIS AUGMENTED REALITY (AR) UNTUK MENINGKATKAN KEMAMPUAN BERPIKIR KRITIS PESERTA DIDIK DI SEKOLAH DASAR - Deviyanti Pangestu; Siti Nuraini; Miranda Abung; Agung Dian Putra (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This problem was driven by the low critical thinking skills of students. This study aimed to analyze the implementation of the use of Augmented Reality (AR)-based teaching materials to improve critical thinking skills in the IPAS subject. The method that was used was quasi-experimental with a non-equivalent control group design. The sample in this study consisted of 54 students who were determined using the saturated sampling technique. The data collection technique used essay test instruments which were then analyzed using a simple linear regression test. The statistical analysis showed that the Fcount value is 54.17 with a significance level of 0.00 < 0.05, so Ho is rejected and Ha is accepted. It could be concluded that the use of Augmented Reality (AR)-based teaching materials was very effective in improving the critical thinking skills in the IPAS subject of fourth grade students at SD Negeri 1 Sepang Jaya.